2017
DOI: 10.1177/2050312117712888
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of walking ability during postoperative rehabilitation with the hybrid assistive limb after total knee arthroplasty: A randomized controlled study

Abstract: Objective:We aimed to compare the efficacies of rehabilitation with the hybrid assistive limb and conventional rehabilitation after total knee arthroplasty.Materials and methods:A total of 37 consecutive patients who underwent primary total knee arthroplasty for knee osteoarthritis were enrolled. Seven patients withdrew from the study after randomization, and 30 patients (hybrid assistive limb group: n = 16; conventional group: n = 14) completed the randomized controlled trial. Patients in the hybrid assistive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 34 publications
0
34
0
1
Order By: Relevance
“… 11 , 12 Recently, the effects of using robotics for walking exercises have been examined, 13 - 15 and exoskeletal robotic exercises have been proposed for patients who have undergone TKA to improve postoperative knee function and walking ability. 16 - 19 However, several of these devices are heavy and have a strong exoskeleton mechanism to provide lower leg support because they are intended to be used during repetitive walking exercises for severely paralyzed patients. As patients after TKA surgery do not have severe paralysis, these exoskeleton-type robotic devices may not be efficient in clinical settings because of the large scale of the devices and time it takes to fit them.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 Recently, the effects of using robotics for walking exercises have been examined, 13 - 15 and exoskeletal robotic exercises have been proposed for patients who have undergone TKA to improve postoperative knee function and walking ability. 16 - 19 However, several of these devices are heavy and have a strong exoskeleton mechanism to provide lower leg support because they are intended to be used during repetitive walking exercises for severely paralyzed patients. As patients after TKA surgery do not have severe paralysis, these exoskeleton-type robotic devices may not be efficient in clinical settings because of the large scale of the devices and time it takes to fit them.…”
Section: Introductionmentioning
confidence: 99%
“…RAGT improved gait independence in stroke and cerebral palsy patients and improved motor function [ 8 , 9 ]. The investigators found the effectiveness of RAGT in patients with musculoskeletal injuries such as knee osteoarthritis [ 10 , 11 ]. Few previous studies have reported the use of RAGT in other musculoskeletal diseases, and there are no clear guidelines regarding the application of RAGT.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Tanaka et al [ 23 ] has been the only randomized controlled trial that compared the lower limb function between groups of patients who underwent training with HAL and conventional therapy after TKA. Although actual measured values were not described in the article, an immediate improvement within 1 week was observed with the use of HAL.…”
Section: Introductionmentioning
confidence: 99%